Vaccine Oka Varicella Meningitis in Two Adolescents - Harrington, Whitney E. (Pediatrics, 2019)
The live-attenuated varicella vaccine, a routine immunization in the United States since 1995, is both safe and effective. Like wild-type varicella-zoster virus, however, vaccine Oka (vOka) varicella can establish latency and reactivate as herpes zoster, rarely leading to serious disease, particularly among immunocompromised hosts. Previous cases of reactivated vOka resulting in meningitis have been described in young children who received a single dose of varicella vaccine; less is known about vOka reactivation in older children after the 2-dose vaccine series. We present 2 adolescents with reactivated vOka meningitis, 1 immunocompetent and 1 immunocompromised, both of whom received 2 doses of varicella vaccine many years before as children. Pediatricians should be aware of the potential of vOka varicella to reactivate and cause clinically significant central nervous system disease in vaccinated children and adolescents.